Key role of different levels of dissolved oxygen in hydrolyzed polyacrylamide bioconversion: Focusing on metabolic products, key enzymes and functional microorganisms. (June 2020) - Zhao, Lanmei; Zhang, Congcong; Lu, Zhiyang; Bao, Mutai; Lu, Jinren
Graphical abstract: Highlights: DO played a short board effect on N bioconversion and HPAM metabolism. HPAM was metabolized to intermediates with various chain length and molecular mass. The maximum of VFA yield, TN removal and enzyme activity occurred in anoxic system. Key enzyme, HPAM metabolism and N bioconversion were closely related. Microbial function was related to HPAM metabolism, N bioconversion and key enzyme. Abstract: Dissolved oxygen (DO) played a short board effect on nitrogen biotransformation and pollutant metabolism. This study for the first time explored the key role of different levels of DO (covering anaerobic, anoxic and aerobic) on hydrolyzed polyacrylamide (HPAM) bioconversion. HPAM was metabolized to intermediates with different chain length. Volatile fatty acid (VFA) production rose first and then descended with DO concentration (0–2 mg·L −1 ), and the maximum reached 92.5 mg·L −1 when DO was 0.5 mg·L −1 . Total nitrogen (TN) removal increased first and then dropped with DO concentration, and the maximum (61.4%) occurred at 0.5 mg·L −1 DO. NH4 + -N dipped from 42.8 to 0 mg·L −1 and NO3 – -N rose from 0 to 32.8 mg·L −1 with DO concentration. The changes of enzyme activities were consistent with those of VFA production and TN removal, which were related to HPAM metabolism and N bioconversion. Microbial function was correlated to HPAM metabolism, N bioconversion and key enzyme.